Formation of the Enterprise’s Sustainable Development Strategy - Mustafadze, Kiamran (Харківський національний автомобільно-дорожній університет, 2025)
The work clarifies the concept of a sustainable development strategy for a road transport enterprise under martial law through the integration of crisis risk-management mechanisms and scenario planning; develops a methodological approach for identifying and prioritizing strategic risks and potentials using unified evaluation scales and integral indices; conducts an analysis of the components of sustainable development of LLC “FFC Persha Stolytsia”; introduces a predictive maintenance system for the vehicle fleet based on telemetry; and provides a technical and economic assessment of the proposed measures.
Keywords: sustainable development; martial law; scenario modeling; crisis risk management; green modernization